Optimist 5 Enterprise: X-Pro toilet brush / Nurnajmi Saifuddin Husani... [et al.] - Husain, Nurnajmi Saifuddin; Shahrunnizam, Nurshahadah; Md Esak, Nuraisyah; Osman, Nur Syaqirah; Mohd Shahrizad, Nursyazwani (2016)
Optimist 5 is a company which focuses on cleaning production in Malaysia. Toilet brush is a tool cleaning toilet bowl. Generally, the toilet brush is used with toilet cleaner or bleach.